CORRELATION OF ECONOMIC INDICATORS OF PROCUREMENT OF AGRICULTURAL PRODUCTS FOR THE NEEDS OF THE DEFENCE SYSTEM - Milunović, Milan; Obradović, Zoran; Rajković, Mile (Economics of Agriculture, 2023)
In the current situation of war conflicts, but also as a consequence of the COVID-19 pandemics, the economic crisis caused by the lack of goods, primarily food, energy sources, weapons and military equipment and multiple other products and services, has induced price increases and inflation. In this regard, there are substantial challenges present in the field of procurement of agricultural products. In that sense, we methodologically included analysis and synthesis, compilations, inductions and deductions of “military budgets”, GDP and some other indicators in several currently most significant countries and in the Republic of Serbia, in the context of compromised global security. The aim is to attain relevant indicators and conclusions which will provide certain guidelines for improvement of procurement of agricultural products for the needs of the defense system in the future.